Pengujian Laju Pembakaran Briket Biomassa Dari Tempurung Kelapa dan Sekam Padi - Fajari, Alfian; Sudarti, Sudarti; Yushardi, Yushardi (Peneliti.net, 2024)
Biomass such as rice husks and coconut shells can be used as a source of raw material for briquettes, which is an alternative energy source from waste. This study aims to determine the combustion rate between briquettes made from coconut shells and rice husks. The method used in this study is a little observation and literature study from several existing journals. The results of this research prove that the combustion rate of coconut shell briquettes is greater than the combustion rate of rice husk briquettes. The results of the briquette burning rate test prove that briquettes made from coconut shells have a greater burning rate than briquettes made from rice husks